"Rollerblade" game As an Effort to Protect the Environment Multiplafrom based - Muhammad Alfin Fikri; Cindy Taurusta (JOINCS (Journal of Informatics, Network, and Computer Science), 2019)
The purpose of this research is to make a smarthphone-based game application media that has been made for them to be more aware of the importance of preserving the environment. Smartphone itself is almost owned by everyone. The smartphone also has an extraordinary ability to play games that are like in video games but can be obtained on a smartphone. The method used is the Research and Development method. The results of the application of this game were directly tested on the field (Car Free Day) by taking the children in the morning and the results were satisfying, on average those who played were very happy and did not feel bored at all. The result is that the existence of the RollerBlade Game is expected to be used as an alternative learning that can later make children aware of the importance of protecting the environment in the lightest way, namely taking the trash that is on the road.